2011
DOI: 10.4028/www.scientific.net/amm.62.85
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the Superficial Laser Shock Peening Treatment Process: Application on a Titanium Aircraft Turbine Engine Blade

Abstract: This paper presents a numerical simulation of the Laser Shock Peening (LSP) process using Finite Element Method (FEM). The majority of the controlling parameters of the process have been taken into account. The LSP loading has been characterized by using a repetitive time Gaussian increment pressure applied uniformly at the impacted zone. The used behavior law of the treated material is supposed Johnson Cook elastic-viscous-plastic coupled with damage. The proposed model leads to obtain the surface modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Frija, M. et al [63] of the University of Sousse, Tunisia used finite element numerical simulations to simulate the effect of LSP on the resistance of Ti-6Al-4V titanium alloy blades to FOD with a square impact region and carried out experimental verification. The results showed that the surface residual compressive stress introduced by LSP significantly improved the high-cycle fatigue performance of titanium alloy fan blades.…”
Section: Research Progress On Fatigue Resistance Of Fan/compressor Bl...mentioning
confidence: 99%
“…Frija, M. et al [63] of the University of Sousse, Tunisia used finite element numerical simulations to simulate the effect of LSP on the resistance of Ti-6Al-4V titanium alloy blades to FOD with a square impact region and carried out experimental verification. The results showed that the surface residual compressive stress introduced by LSP significantly improved the high-cycle fatigue performance of titanium alloy fan blades.…”
Section: Research Progress On Fatigue Resistance Of Fan/compressor Bl...mentioning
confidence: 99%
“…The calculation of the reliability is carried out based on the "Constraint-Resistance" approach by the numerical method of Monte-Carlo random selections. For this, we used and validated the deterministic model developed in the works of Frija et al 16,17 The Crossland criterion is defined for a high cycle rate (usually taken to be equal to 10 7 cycles and for a 50% confidence level). It is defined by a linear combination of the amplitude of ffiffiffiffiffiffiffi J 2,a p and the maximum hydrostatic pressure P max .…”
Section: Approach and Identification Of Requirementmentioning
confidence: 99%
“…The calculation of the reliability is carried out based on the “Constraint‐Resistance” approach by the numerical method of Monte‐Carlo random selections. For this, we used and validated the deterministic model developed in the works of Frija et al 16,17 …”
Section: Approach and Identification Of Requirementmentioning
confidence: 99%